Configurations of Peruvian Female Migration in Iquique, Chile, in the 21st Century - Lube-Guizardi, Menara; Nazal-Moreno, Esteban; Valdebenito-Tamborino, Felipe; López-Contreras, Eleonora (Papeles de Población; Vol. 23 Núm. 94 (2017): Papeles de Población, 2018)
The article presents a state-of-the-art of studies about the Peruvian female migration in Iquique (Region of Tarapacá, Chile). Through the synthesis of qualitative and quantitative research, we offer the contextualization of social, economic and political processes that endorses the interpretation of available demographic data. We will situate the geographical limits, the political-administrative and ecological characteristics of Tarapacá and will problematize the notion that the migration in Iquique is a novel phenomenon. We will synthesize the local economic characteristics and their relationship with the sociodemographic characteristics, the labor insertion and the social networks of the Peruvian migrant population. We conclude the text by pointing out how national and ethnic identity processes are configured in Iquique, stressing the reproduction of asymmetries and frictions of alterity between Peruvian woman and Chileans.